The respiration of the anterior byssus refractor muscle of Mytilus edulis (ABRM) after a phasic contraction - Baguet, F. (1967)
1. The oxygen consumption of isolated anterior byssus retractor muscle of Mytilus edulis (ABRM) has been measured at rest and after phasic contractions induced by a.c. stimulation. 2. The respiration was measured with a Clark oxygen electrode in successive periods of 5 or 15 min, at 20° C. 3. The resting respiration is 71·8 ± 2·4 n-moles O(2)/g wet weight.min (mean ± S.E., n = 70). It is increased by a release and decreased by a passive stretch. 4. After phasic stimulation of up to 30 sec the respiration is increased and returns to a slightly higher level than the resting level in an exponential fashion with a time constant of about 10 min. 5. The duration of stimulation does not change the time course of the excess respiration but it affects its magnitude. The amount of extra oxygen consumed, in n-moles O(2)/g, is made up of a constant amount, 449 ± 102, and an amount that depends on the duration of stimulation (t, sec), which is given by t × 13·2 ± 4·3. When due account is taken for the tension developed, these parameters become 83·1 ± 20·7 and t × 1·24 ± 0·66 n-moles O(2)/g muscle and kg/cm(2) of tension. This regression analysis is based on forty-eight data, with a residual error based on 5 degrees of freedom. 6. Release of the tension after the last stimulus of a 30 sec tetanus reduces by half the extra oxygen consumed during the recovery whereas the same release applied 5 min later has a much smaller effect. This suggests that relaxation is an active process. 7. From these measurements of the recovery metabolism the energy cost of the contraction was estimated and compared with this cost in vertebrate striated muscle. The constant item has about the same magnitude, but the item related to the duration of stimulation is about 250 times smaller.